Association between hyperuricemia and long-term mortality in patients with hypertension: results from the NHANES 2001–2018 - Yin, Yufeng; Zhou, Erye; Wu, Jian (Frontiers in Cardiovascular Medicine, 2024)
Objective: The prevalence of hyperuricemia and hypertension is steadily increasing, and these conditions often share common risk factors. This study aimed to investigate the association among hyperuricemia, hypertension, and all-cause mortality in a nationally representative U.S. population. Methods: Data for 38,644 participants were obtained from the National Health and Nutrition Examination Survey (NHANES) 2001-2018. Hyperuricemia was defined as a serum urate concentration >420 μmol/L in men and >360 μmol/L in women. Information regarding death outcomes was obtained through the National Death Index (NDI). Multivariate logistic regression, Cox proportional hazards models, and restricted cubic spline (RCS) analyses were used to evaluate the association between hyperuricemia and hypertension in all included participants, as well as long-term mortality in patients with hypertension. Results: Among all participants, 6956 (18.0%) had hyperuricemia, while 31,688 (82.0%) had nonhyperuricemia. According to the adjusted models, hyperuricemia was more strongly associated with hypertension (OR 2.04) than was non-hyperuricemia. During the median follow-up period of 78 months, both hyperuricemia (HR 1.48, 1.95) and hypertension (HR 1.42, 1.69) independently associated with the increased risk of all-cause mortality and cardiovascular mortality, respectively, with the highest risk observed in those with both conditions (HR 1.87, 2.82). RCS analyses revealed nonlinear J-shaped (for hypertension) and U-shaped (for both all-cause and cardiovascular mortality) relationships with serum urate levels. Conclusions: Hyperuricemia is associated with an elevated risk of developing hypertension compared to non-hyperuricemia. Among patients with hypertension, those with hyperuricemia are more likely to experience all-cause and cardiovascular mortality during long-term follow-up.